On lower-back pain and its consequence to productivity - Ramdan, Nur Sufiah Akmala; Bani Hashim, Ahmad Yusairi; Kamat, Seri Rahayu; Ali Mokhtar, Mohd Najib; Asmai, Siti Azirah (Engineering and Technology Publishing, 2014)
Manual handling is the primary cause of musculoskeletal disorders, such as sprains and strains and joint disorders, which account for more than half of all injury claims. If motions are repeated frequently, such as in every few seconds, and for prolonged periods such as an eight-hour shift, fatigue and muscle strain can acquire. Working hours is lost every year by means of injury, and personal injury situations and compensation packets are costly. Employers could boost productivity by training their workers to handle loads the right way, or by providing materials-handling equipment to aid them with the job.